Protection of yttria-stabilized zirconia for dental applications by oxidic PVD coating. (1st January 2015) - Hübsch, C.; Dellinger, P.; Maier, H.J.; Stemme, F.; Bruns, M.; Stiesch, M.; Borchers, L.
Graphical abstract: Abstract: In this study, the application of transparent physical vapor deposition (PVD) coatings on zirconia ceramics was examined as an approach to retard the low-temperature degradation of zirconia for dental applications. Transparent monolayers of titanium oxide (Tix Oy ) and multilayers consisting of titanium oxide–alumina–titanium oxide (Tix Oy –Alx Oy –Tix Oy ) were deposited onto standardized discs of 3Y-TZP using magnetron sputtering. Using X-ray photospectroscopy and time-of-flight secondary-ion mass spectrometry, the compositions of the coatings were verified, and an approximate thickness of 50 nm for each type of coating was ascertained. After aging the coated and uncoated samples in water vapor at 134 °C and 3 bar for 4, 8, 16, 32, 64 and 128 h, the monoclinic phase content was determined using X-ray diffraction, and its impact on mechanical properties was assessed in biaxial flexural strength tests. In addition, the depth of the transformation zone was measured from scanning electron microscopy images of the fracture surfaces of hydrothermally aged samples. The results revealed that the tetragonal-to-monoclinic phase transformation of the zirconia ceramic was retarded by the application of PVD coatings. During the first stages of aging, the coated samples exhibited a significantly lower monoclinic phase content than the uncoated samples and, after 128 h of aging, showed a transformation zone which was only ∼12–15 μm thick compared to ∼30 μm in the control group. Biaxial flexural strength decreased by ∼10% during aging and was not influenced by the application of a PVD coating.